Air pollution and stroke: Short-term exposure's varying effects on stroke subtypes - Minqi Liao; Siqi Zhang; Cheng He; Susanne Breitner; Josef Cyrys; Markus Naumann; Lino Braadt; Claudia Traidl-Hoffmann; Gertrud Hammel; Annette Peters; Michael Ertl; Alexandra Schneider (Ecotoxicology and Environmental Safety)
Background: Few studies have examined how air pollutants affect various stroke subtypes and how these effects differ with stroke severity, especially among European populations living in less polluted areas. Methods: We conducted a time-stratified case-crossover study using 15 years of hospital-based stroke data from the University Hospital Augsburg in Southern Germany. Daily average air pollutants, including particulate matter (PM) with an aerodynamic diameter < 10μm (PM10), coarse particles (PMcoarse), fine particles (PM2.5), ozone (O3), nitrogen oxides (NO2, NO), and meteorological data were obtained from local fixed urban background monitoring sites from 2006 to 2020. Conditional logistic regression was utilized to estimate the relationship between pollutants and daily stroke events, with modification effects being examined through stratified and interaction analyses. Results: Based on 19,518 included stroke cases, each interquartile range (IQR) increase in PM2.5, PM10, PMcoarse, and NO2 was associated with a 2.11 %, 2.55 %, 2.50 %, and 3.48 % rise in overall stroke events 5–6 days later. Positive associations were seen mostly for transient ischemic attacks and hemorrhagic strokes. Notably, people with severe stroke-induced disabilities were disproportionately affected by PM and NO2, while those with mild disabilities were more affected by O3 and NO. Moreover, damaging effects were amplified during warm seasons and the 2016–2020 five-year period. Conclusion: Short-term air pollution exposure may trigger stroke events, with differential impacts depending on stroke subtype and severity of pre-existing disability. A coordinated effort is needed for stroke prevention in response to specific air pollutants, especially in the context of global warming.